The archaeology of the Kurdistan Region of Iraq and adjacent regions - Kopanias, Kōnstantinos; MacGinnis, John (Archaeopress, 2016)
Conference proceedings presenting the first opportunity for leading figures in the burgeoning area of archaeological research in the Kurdish Autonomous Region of Iraq to gather and present all the key new projects which are revolutionising our understanding of the region
Conference proceedings. - Previously issued in print: 2016. - Available through Archaeopress Digital Subscription Service. - Description based on online resource; title from home page (viewed on November 9, 2016)
Specialized
Keywords: Kurdistān (Iraq) -- Congresses -- Antiquities; Kurdistān (Iraq) -- Congresses -- Civilization -- Iraq -- Kurdistān; Kurdistān (Iraq) -- Antiquities -- Congresses; Kurdistān (Iraq) -- Civilization -- Congresses; Konferenzschrift -- 01.11.2013-03.11.2013 -- Athen; Ausgrabung; Kurdistan